The Influence of the Pilates Method on the Quality of Life of its Practitioners: A Systematic Review - Fabrício Sette Abrantes Silveira; Lívia Carvalho Sette Abrantes; Osvaldo Moreira Costa; Pedro Paulo do Prado Júnior; Flávio de Jesus Camilo; Felipe José Aidar; Eveline Torres Pereira (Motricidade, 2022)
Introduction: Created in Germany by Joseph Pilates in the 1920s, the Pilates Method (PM) uses exercises that aim to improve physical health and mental balance. Objective: To verify, through a systematic literature review without delineating languages ​​and dates, the influence of PM on the quality of life (QoL) of its practitioners. Methods: Medline, Embase, Web of Science, Scopus, and Google Scholar databases were consulted. The articles were independently selected by two researchers, who also conducted the risk of bias assessment of the articles included. Results: 2848 articles were identified on the databases, of which 30 were included in the study synthesis. Conclusion: The practice of PM improves the QoL of its practitioners, providing enhanced functional capacity, pain relief, and improvement of emotional aspects in individuals of both sexes, different age groups, and different clinical contexts.